The Relationship between Mindfulness Level and some Demographic Variables among Students of University - Aladsani, Lamia A. (Journal of Ecohumanism, 2024)
This study aimed to reveal the levels of mindfulness among the study participants and to examine the differences in the levels of mindfulness among the participants according to three demographic variables, namely gender, type of college, and academic level, and the interactions between these variables. In total, 275 university students in the Kingdom of Saudi Arabia participated in the study. Using a random sample, data were collected using a mindfulness scale. Based on the results of the study, it can be concluded that the participants had an average level of mindfulness. The findings also revealed no differences in mindfulness attributable to gender, type of college, or academic level or the interactions between all these variables. The study’s results can provide benefits by increasing young people’s awareness of the importance of alertness and presence of mind for a healthy life, in addition to generating interest in organizing training programs inside or outside universities, aimed at improving students’ levels of mindfulness and providing intensive training.